Nanorod-shaped Cu1.8S material as well as preparation method and application thereof
Through the simple Cu1.8S nanorod directional synthesis technology under normal temperature, the problem of stoichiometric ratio control and crystal morphology design in the prior art is solved, and efficient and controllable nanorod material preparation is achieved. Excellent photoelectric performance and wide application prospects.
Patent Information
- Application Number
- CN202411513134.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-07
AI Technical Summary
The prior art is difficult to meet the stoichiometric ratio control and crystal morphology design of Cu2-xS copper sulfide Cu2-xS, resulting in complex synthesis methods, insufficient control accuracy and low product purity.
A simple Cu1.8S nanorod directional synthesis technology under normal temperature conditions was adopted. By adding ascorbic acid to copper ion solution, Na2S or K2S, stirring reaction, centrifugation and washing, nanorod Cu1.8S material was obtained.
It has achieved efficient and controllable preparation of Cu1.8S nanorod materials, with high specific surface area, stable p-type semiconductor characteristics and optimized photoelectric properties, and is suitable for thermoelectric, photocatalysis and water treatment fields.
Smart Images

Figure CN119390107A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of optoelectronic materials, and particularly relates to a nanorod-shaped Cu 1.8 S material and its preparation method and application. Background Art
[0002] Copper sulfide (Cu 2-x S) has attracted much attention due to its important application in photovoltaic cells. By adjusting its stoichiometric ratio, Cu 2-x S can change the band gap and structure. Its stoichiometric factor (2-x) varies from 1 to 2, covering the range from copper-rich chalcocite (Cu 2 S) to copper-poor azurite (CuS), and the intermediate phases include dulphite (Cu 1.97 S), bornite (Cu 1.8 S) and anthracene (Cu 1.4 S) etc. This type of Cu 2-x S nanocrystals have p-type semiconductor properties due to the copper vacancies in the crystal lattice, which is the main reason for their widespread use in optoelectronic devices.
[0003] Studies have shown that Cu 2-x The band gap of S is dependent on the stoichiometric ratio: as the x value increases, the band gap of copper sulfide gradually increases, and chalcocite (Cu 2 S) has a band gap of 1.2 eV, and bornite (Cu 1.8 S) is 1.5eV, while azurite (CuS) reaches 2.0eV. 2-x The composition of S can optimize its photoelectric properties.
[0004] In addition, the crystal morphology of copper sulfide materials (such as nanowires, nanosheets, nanorods, etc.) significantly affects their photoelectron transport performance. A larger surface area helps to improve light absorption efficiency, while a specific morphology is conducive to the efficient transmission and separation of photoelectrons and holes. Therefore, regulating the morphology of copper sulfide can not only enhance its light absorption ability, but also optimize the migration path of photogenerated electrons and improve the overall photoelectron performance.
[0005] However, there are still limited synthesis methods that can simultaneously meet the requirements of stoichiometric ratio control and crystal morphology design. The existing technology often has problems such as complex steps, insufficient control accuracy and low product purity. In response to this challenge, the present invention proposes a simple Cu1.8S nanorod directional synthesis technology at room temperature to achieve efficient and controllable material preparation. Summary of the invention
[0006] In view of the shortcomings of the prior art, the present invention aims to provide a nanorod-shaped Cu 1.8S (copper-rich copper sulfide) material and its preparation method and application. The preparation method of the present invention is simple and can prepare nanorod-shaped copper-rich copper sulfide Cu by reaction at room temperature. 1.8 S; Nanorod-shaped Cu prepared by the present invention 1.8 The S material belongs to the hexagonal system, and the Cu center and the first coordinated S atom form three average bond lengths The Cu-S coordination of the synthesized material meets the requirements of Cu 1.8 The crystal characteristics of S are nanorod-shaped with a high specific surface area. This material has application prospects in thermoelectricity, photocatalysis and water treatment.
[0007] The purpose of the present invention is achieved through the following technical solutions:
[0008] The present invention provides a nanorod-shaped Cu 1.8 The preparation method of S material comprises the following steps:
[0009] Ascorbic acid was added to the copper ion solution, followed by the addition of Na 2 S or K 2 S, stirring reaction, centrifugation, washing, to obtain nanorod-shaped Cu 1.8 S material;
[0010] The pH of the copper ion solution is 2-4.
[0011] Preferably, the pH of the copper ion solution is 4. At this time, the material is more stable during the synthesis process, the coagulation degree is lower, the hydraulic radius is smaller, and the synthesized material has a larger specific surface area, which is conducive to the conduction of photoelectricity.
[0012] Preferably, the concentration of copper ions in the copper ion solution is 50-300 mg / L.
[0013] Further preferably, the concentration of copper ions in the copper ion solution is 100 mg / L.
[0014] Preferably, the dissolved oxygen content of the copper ion solution is less than or equal to 0.2 ppm. The dissolved oxygen content of the solution is reduced by continuously bubbling nitrogen into the solution.
[0015] Preferably, the ascorbic acid is added in an amount such that the redox potential of the solution is less than or equal to 0.1V.
[0016] Further preferably, the ascorbic acid is added in an amount such that the redox potential of the solution is equal to 0.1V.
[0017] Preferably, the stirring rate when adding ascorbic acid is 50-100 rpm.
[0018] Preferably, Na 2 S or K 2The molar ratio of S to copper ions is 0.5-0.8:1;
[0019] Further preferably, Na 2 S or K 2 The molar ratio of S to copper ions is 1:2;
[0020] Preferably, Na is added 2 S or K 2 The stirring rate at S is 350-400 rpm.
[0021] Preferably, the stirring reaction rate is 50-100 rpm;
[0022] Preferably, the stirring reaction time is 30-60 min;
[0023] Preferably, the stirring reaction is carried out at room temperature.
[0024] The present invention provides a nanorod-shaped Cu prepared by the above-mentioned preparation method 1.8 S material.
[0025] Preferably, the nanorod-shaped Cu 1.8 The main component of S material is Cu 1.8 S, single Cu 1.8 The S crystal material has a rod-like morphology, a length of 50-150nm, belongs to the hexagonal crystal system, and has a lattice spacing of 0.278nm.
[0026] The present invention provides the above-mentioned nanorod-shaped Cu 1.8 Application of S materials in thermoelectricity, photocatalysis and water treatment.
[0027] Compared with the prior art, the advantages and beneficial effects of the present invention are as follows:
[0028] Efficient preparation: The present invention provides a simple Cu1.8S nanorod directional synthesis technology at room temperature, which reduces the complicated process steps in the traditional method and improves the production efficiency. This method is easy to operate and is conducive to large-scale production and application.
[0029] Controllable stoichiometric ratio: The present invention can precisely control the stoichiometric ratio of Cu1.8S through the synthesis technology to ensure the band gap and structural consistency of the material. This precise control can optimize the photoelectric properties of the material, making it more suitable for photoelectric devices such as photovoltaic cells.
[0030] Unique crystal morphology: The Cu1.8S material prepared by the present invention has a nanorod morphology, a small size, and a large specific surface area, which helps to improve the light absorption efficiency. At the same time, the morphology of the nanorod is conducive to the efficient transmission and separation of photogenerated electrons and holes, further enhancing the photoelectronic performance of the material.
[0031] Stable p-type semiconductor properties: The copper vacancies in the Cu1.8S nanorods prepared by the present invention give them stable p-type semiconductor properties, which are suitable for application in a variety of optoelectronic and photovoltaic fields and have broad application potential.
[0032] Bandgap optimization: The Cu1.8S prepared by the present invention has a moderate bandgap of 1.5 eV. Combined with its morphology design, it has excellent light absorption and carrier migration capabilities in the photoelectric conversion process, providing an ideal material choice for high-efficiency photoelectric devices.
[0033] High material purity and consistency: Compared with the prior art, the Cu1.8S nanorod material synthesized by the present invention has higher purity and structural consistency, which solves the problems of insufficient control accuracy and low product purity in traditional methods and improves the repeatability of material performance.
[0034] In summary, the advantage of the present invention lies in the material preparation method, which not only simplifies the synthesis process of Cu1.8S material, but also improves the photoelectric properties of the material by precise control of the stoichiometric ratio and crystal morphology, overcomes the key difficulties in the prior art, and has significant technological progress and practical application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 The nanorod-shaped Cu prepared in Example 1 1.8 X-ray diffraction spectrum, X-ray photoelectron scattering spectrum and synchrotron radiation spectrum of S material.
[0036] Figure 2 The nanorod-shaped Cu prepared in Example 1 1.8 High-resolution electron microscopy image of S material. DETAILED DESCRIPTION
[0037] The specific implementation of the present invention is further described below in conjunction with the accompanying drawings and examples, but the implementation and protection of the present invention are not limited thereto. It should be noted that if there are processes that are not particularly described in detail below, they can be implemented or understood by those skilled in the art with reference to the prior art. If the manufacturer of the reagents or instruments used is not indicated, they are deemed to be conventional products that can be purchased commercially.
[0038] Example 1
[0039] This embodiment provides a nanorod-shaped Cu 1.8 The preparation method of S (copper-rich copper sulfide) material comprises the following steps:
[0040] Step 1: Prepare a solution with pH 2 using HCl;
[0041] Step 2: Add copper chloride to the pH 2 solution to make the copper ion concentration 100 mg / L;
[0042] Step 3: By continuously bubbling nitrogen into the solution, the dissolved oxygen content of the solution is reduced to 0.2 ppm to obtain solution A;
[0043] Step 4: Add 1mmol / L AA solution to solution A, and measure the oxidation-reduction potential (ORP) of the solution in real time. When adding liquid, ensure that the stirring rate of the solution is maintained at 50rpm to make AA dispersed evenly in the solution. When the ORP of the solution drops to 0.1V, stop adding AA to obtain solution B;
[0044] Step 5: Rapidly add 25mmol / L Na 2 S solution, so that the molar ratio of Cu and S in the solution is 2:1, and the stirring rate of the solution is maintained at 400 rpm during the addition of liquid, and the stirring is continued at 50 rpm for 60 min at room temperature;
[0045] Step 6: After the reaction is completed, centrifuge, add deionized water, shake, and centrifuge. Repeat this process several times to obtain nanorod-shaped copper-rich copper sulfide Cu 1.8 S material.
[0046] To clarify the nanorod-shaped copper-rich copper sulfide Cu 1.8 The structure of S material is determined by X-ray diffraction spectrum, high-resolution transmission electron microscopy, X-ray photoelectron spectroscopy and extended X-ray absorption fine structure spectrum.
[0047] X-ray diffraction (XRD) pattern results ( Figure 1 a) in the figure shows that the obtained nanorod-shaped copper-rich copper sulfide Cu 1.8 The mineral crystal form of S material shows the characteristics of bornite (Cu 1.8 S).
[0048] X-ray photoelectron S2p fine spectrum shows nanorod-like copper-rich copper sulfide Cu 1.8 The sulfur in the S material is mainly negative divalent sulfur (S 2- ), disulfide (S 2 2- ) and polysulfide (S n 2- )( Figure 1 b) Cu 3d fine spectrum shows that nanorod-shaped copper-rich copper sulfide Cu 1.8 Cu in S material is a mixed valence state of Cu(Ⅰ) and Cu(0) ( Figure 1c). X-ray absorption near-edge spectroscopy (XANES) and extended X-ray absorption fine structure (EXAFS) confirmed the Cu x Different oxidation states and coordination situations of Cu in S. Figure 1 The inset in d shows the Cu 0 , CuS and Cu x The front edge energy position of the K absorption edge XANES spectrum of Cu in S changes, and the resulting nanorod-shaped copper-rich copper sulfide Cu 1.8 The difference in the energy position of the front edge of the absorption edge of the S material is the highest, indicating that the Cu atoms in the material have a larger number of coordinated Cu-S bonds than the number of CuS.
[0049] Nanorod-shaped copper-rich copper sulfide Cu 1.8 k of S material 3 Wavelet transform (WT) of weighted EXAFS spectra ( Figure 1 e) in the display, located at The intensity is the maximum at , which corresponds to Cu-S coordination, but there is no intensity corresponding to Cu-O and Cu-Cu. 1.8 The FEFF function of S material is similar to that of the standard Cu 1.8 S (JCPDS card No.47–1748) Figure 1 f). The Fourier transform results clearly show that the nanorod-shaped copper-rich copper sulfide Cu 1.8 The main peaks of S material appear in The peak corresponding to the Cu-S coordination peak is not observed. 2 O(Cu-O: )、Cu(0)(Cu-Cu: ) peak, indicating that the nanorod-shaped copper-rich copper sulfide Cu 1.8 S material does not contain Cu(0), further proving that Figure 2 Nanorod-shaped copper-rich copper sulfide Cu 1.8 The peaks of S material at 931.0eV and 932.8eV should be attributed to Cu(Ⅰ). x The shift of the Cu-S peak to low R indicates that it is due to Cu x The average bond length of Cu-S bonds in S is significantly shortened, and the fitting results show that the nanorod-shaped copper-rich copper sulfide Cu 1.8 The average bond length between the Cu center of the S material and the first coordinated S atom is Cu-S coordination (coordination number is 3).
[0050] Single Cu was observed by high-resolution transmission electron microscopy 1.8 The S particles present a nanorod structure with a length of about 100 nm ( Figure 2 a), the lattice spacing is 0.278nm ( Figure 2 c) in Cu 1.8 The resulting nanorod-shaped copper-rich copper sulfide Cu 1.8 The fast Fourier transform (FFT) pattern of the S material shows a hexagonal spot array, and the STEM image is similar to that of the Cu 1.8 The Cu atoms in S crystals are arranged in the same way along the
[0001] crystal axis ( Figure 2 d) in.
[0051] Example 2
[0052] This embodiment provides a nanorod-shaped Cu 1.8 The preparation method of S (copper-rich copper sulfide) material comprises the following steps:
[0053] Step 1: Prepare a solution with pH 3 using HCl;
[0054] Step 2: Add copper chloride to the pH 3 solution to make the copper ion concentration 100 mg / L;
[0055] Step 3: By continuously bubbling nitrogen into the solution, the dissolved oxygen content of the solution is reduced to 0.2 ppm to obtain solution A;
[0056] Step 4: Add 1mmol / L AA solution to solution A and measure the ORP of the solution in real time. When adding liquid, ensure that the stirring rate of the solution is maintained at 50rpm to make AA dispersed evenly in the solution. When the ORP of the solution drops to 0.1V, stop adding AA to obtain solution B;
[0057] Step 5: Rapidly add 25mmol / L Na 2 S solution, so that the molar ratio of Cu and S in the solution is 2:1, and the stirring rate of the solution is maintained at 400 rpm during the addition of liquid, and the stirring is continued at 50 rpm for 60 min at room temperature;
[0058] Step 6: After the reaction is completed, centrifuge, add deionized water, shake, and centrifuge. Repeat this process several times to obtain nanorod-shaped copper-rich copper sulfide Cu 1.8 S material.
[0059] Example 3
[0060] This embodiment provides a nanorod-shaped Cu 1.8 The preparation method of S (copper-rich copper sulfide) material comprises the following steps:
[0061] Step 1: Prepare a solution with pH 4 using HCl;
[0062] Step 2: Add copper chloride to the pH 4 solution to make the copper ion concentration 100 mg / L;
[0063] Step 3: By continuously bubbling nitrogen into the solution, the dissolved oxygen content of the solution is reduced to 0.2 ppm to obtain solution A;
[0064] Step 4: Add 1mmol / L AA solution to solution A, and measure the oxidation-reduction potential (ORP) of the solution in real time. When adding liquid, ensure that the stirring rate of the solution is maintained at 50rpm to make AA dispersed evenly in the solution. When the ORP of the solution drops to 0.1V, stop adding AA to obtain solution B;
[0065] Step 5: Rapidly add 25mmol / L Na 2 S solution, so that the molar ratio of Cu and S in the solution is 2:1, and the stirring rate of the solution is maintained at 400 rpm during the addition of liquid, and the stirring is continued at 50 rpm for 60 min at room temperature;
[0066] Step 6: After the reaction is completed, centrifuge, add deionized water, shake, and centrifuge. Repeat this process several times to obtain nanorod-shaped copper-rich copper sulfide Cu 1.8 S material.
[0067] When the pH is 2, 3, and 4, nanorod-shaped copper-rich copper sulfide Cu 1.8 The proportion of Cu and S in the S material remains unchanged, and the surface zeta potential is -28.6, -41.5, and -43.3 mV, respectively. It can be seen that when the pH is 4, the nanorod-shaped copper-rich copper sulfide Cu 1.8 S materials have higher stability and lower agglomeration during the synthesis process. 1.8 The hydrodynamic radius of S material during the synthesis process was found to increase to 2200, 1600 and 1500 nm respectively within 20 minutes when the pH was 2, 3 and 4. The lower the degree of coagulation during the synthesis process, the smaller the hydrodynamic radius, and the synthesized material has a larger specific surface area, which is conducive to the conduction of photoelectricity.
[0068] The above embodiments are only preferred implementation modes of the present invention and are only used to explain the present invention rather than to limit the present invention. Any changes, substitutions, modifications, etc. made by those skilled in the art without departing from the spirit of the present invention should fall within the scope of protection of the present invention.
Claims
1. A nanorod-shaped Cu 1.8 The method for preparing S material is characterized in that: The following steps are involved: Ascorbic acid is added to the copper ion solution, and then Na2S or K2S is added, stirred for reaction, centrifuged, and washed to obtain nanorod-shaped Cu 1.8 S material; The pH of the copper ion solution is 2-4.
2. The preparation method according to claim 1, characterized in that: The concentration of copper ions in the copper ion solution is 50-300 mg / L.
3. The preparation method according to claim 1, characterized in that: The dissolved oxygen content of the copper ion solution is less than or equal to 0.2 ppm.
4. The preparation method according to claim 1, characterized in that: The ascorbic acid is added in an amount such that the redox potential of the solution is less than or equal to 0.1V.
5. The preparation method according to claim 1, characterized in that: The stirring rate during the addition of ascorbic acid was 50-100 rpm.
6. The preparation method according to claim 1, characterized in that: The molar ratio of Na2S or K2S to copper ions is 0.5-0.8:1; The stirring rate when adding Na2S or K2S was 350-400 rpm.
7. The preparation method according to claim 1, characterized in that: The stirring reaction rate is 50-100 rpm; The stirring reaction time is 30-60min; The stirring reaction was carried out at room temperature.
8. The nanorod-shaped Cu prepared by the preparation method according to any one of claims 1 to 7 1.8 S material.
9. The nanorod-shaped copper-rich copper sulfide material according to claim 8, characterized in that: The nanorod-shaped Cu 1.8 The main component of S material is Cu 1.8 S, single Cu 1.8 The S crystal material has a rod-like morphology, a length of 50-150nm, belongs to the hexagonal crystal system, and has a lattice spacing of 0.278nm.
10. The nanorod-shaped Cu according to claim 8 or 9 1.8 Application of S materials in thermoelectricity, photocatalysis and water treatment.